1995
DOI: 10.1139/f95-520
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection of fish with larval sealworm, Pseudotertanova decipiens (Nematoda, Anisakinae), transmitted by amphipods

Abstract: Larval sealworm (Pseudoterranova decipiens, (Krabbe 1878)) were transmitted sequentially through copepods and amphipods to 12 phylogenetically diverse fish species. Although P. decipiens in amphipods were 0.82–7.08 mm long, only those ≥1.41 mm were infective to fish. Sealworm transmitted at 15 °C migrated to the musculature within 6 h in mummichog (Fundulus heteroclitus) and 12 h in rainbow smelt (Osmerus mordax) but were confined to the bolus in an Atlantic cod (Gadus morhua) stomach at 24 h. All sealworm in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 27 publications
0
37
0
Order By: Relevance
“…In a further set of experiments, McClelland (1995) demonstrated that only worms larger than 1.41 mm in length, and usually larger than 2.00 mm, were infective to fish. As sealworms cannot attain this size in microinvertebrate hosts such as copepods, these results imply that macroinvertebrates are an essential component of transmission.…”
Section: E Ex Xp Pe Er Ri Im Me En Nt Ta Al L R Re Ec Co or Rd Ds Smentioning
confidence: 93%
“…In a further set of experiments, McClelland (1995) demonstrated that only worms larger than 1.41 mm in length, and usually larger than 2.00 mm, were infective to fish. As sealworms cannot attain this size in microinvertebrate hosts such as copepods, these results imply that macroinvertebrates are an essential component of transmission.…”
Section: E Ex Xp Pe Er Ri Im Me En Nt Ta Al L R Re Ec Co or Rd Ds Smentioning
confidence: 93%
“…In addition, associations between the prevalence of sealworm infections in commercial fish and seal populations are not fully understood (McClelland, 2002). Other abiotic factors, such as water temperature, are important in transmission (McClelland, 1982(McClelland, , 1990(McClelland, , 1995Measures, 1996;McClelland and Martell, 2001;McClelland, 2002).…”
Section: Patterns and Trendsmentioning
confidence: 99%
“…For example, 12 different species of fish (marine, anadromous, and freshwater) including Atlantic salmon, brook trout, rainbow smelt, and Atlantic cod were susceptible to experimental infections by P. decipiens using experimentally infected amphipod intermediate hosts (McClelland, 1995). In some fish such as rainbow smelt, tissue responses to infections were absent.…”
Section: Fish and Invertebratesmentioning
confidence: 99%
See 2 more Smart Citations